Satyavati: The Enigmatic Woman in Kavita Kane’s The Fisher Queen’s Dynasty - Sow Mondal, Krishna Chatur; Lavanya, S. (International Journal of Psychosocial Rehabilitation, 2024)
This paper explores the presentation of myth in Kavita Kane’s The Fisher Queen’s Dynasty (2017). Myth is represented from a different perspective. The story of mythical characters is no more that of Gods and Goddesses, Kane portrays them as flesh and blood human beings. Interestingly Kane’s novels portray and bring to the forefront the marginal character of Indian Mythology, such as, Satyavati the female lead in the current study, The Fisher Queen’s Dynasty. Using mythology as a background, foregrounding the condition of women in a patriarchal social order, the novelist Kavita Kane highlights the quest of women for their identity as a dominant theme of this novel. The paper explores the pivotal role played by the protagonist Satyavati in shaping the plot and the subsequent turn of events and incidents in the novel. The paper further elucidates the journey of Satyavati from being mere fisherwomen to that of the queen of the Hastinapur.